Fabrication of silk reservoir implants for sustained drug delivery and other applications - Wolfe, Alexander. (2018)
Abstract: In the modern era of medicine there exist numerous approaches to safe, efficacious drug delivery. Implantable systems containing reservoirs of drug offer several advantages over traditional oral regimens, including improved drug bioavailability, limited systemic toxic effects of potent therapeutics through local implantation, modulated and multi-phase release, and reduced dosing frequencies allowing for enhanced patient compliance. Furthermore, sustained delivery implants have the ability to secrete drug at a near-constant release rate over long periods, providing even more robust alternatives to chronic oral medications. The materials used to construct these systems, however, can exhibit several shortcomings; they are often not bioresorbable and thus require a secondary surgery to remove from the body, and can sometimes only be generated by fabrication processes that require harsh chemical solvents. Here, a novel fabrication process to create biodegradable drug reservoir systems made from regenerated silk fibroin protein solution (23% w/v) is demonstrated. Loadable systems (inner diameter 3.0 mm; wall thickness < 250µm) were developed in a reproducible manner using an all-aqueous solution-gel-solid phase transition curing process, and released two different clinically-relevant therapeutics at a near-constant rate for 30 days (> 100µg / day). Systems were analyzed for both their chemical and mechanical characteristics - analysis of crystalized protein secondary structure revealed the systems to be of similar composition compared to previously-generated solid silk materials, while radial compression (1mm / min) testing of unloaded systems suggests they have a range of Young's modulus values similar to cancellous (spongy) bone (100 - 250 MPa), which is relevant when considering potential implantation sites of functional systems. These silk reservoirs demonstrated a degree of compliance when placed under cyclic compression (12.5mHz up to 17.5% strain), and are the first solid silk materials to be generated as "complex" shapes (hollow cylinders) via an additive molding manufacturing process. Therefore, this fabrication approach has the potential to be leveraged for applications outside of drug delivery including in the areas of tissue engineering and diagnostic sensing.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Chris Rogers.; Committee: David Kaplan, and Jeffrey Guasto.; Keywords: Biomedical engineering, Biomechanics, and Materials Science.